Cognitive Impairment After Resolution of Hepatic Encephalopathy: A Systematic Review and Meta-Analysis - López-Franco, Óscar; Morin, Jean-Pascal; Cortés-Sol, Albertina; Molina-Jiménez, Tania; Del Moral, Diana I.; Flores-Muñoz, Mónica; Roldán-Roldán, Gabriel; Juárez-Portilla, Claudia; Zepeda, Rossana C. (Frontiers in Neuroscience, 2021)
Hepatic encephalopathy (HE) is one of the most disabling metabolic diseases. It consists of a complication of liver disease through the action of neurotoxins, such as excessive production of ammonia from liver, resulting in impaired brain function. Prevalence as well as incidence is not well known, although it has been established that up to 40% of cirrhotic patients develop HE. Patients with HE episodes display a wide range of neurological disturbances, from subclinical alterations to coma. There is robust evidence about the cognitive problems showed in HE patients, and how these problems are worsening in overt HE patients. However, there is a discussion regarding whether the resolution of hepatic disease restores cognitive function. Therefore, the aim of this review was to evaluate the degree to which cirrhotic patients with a history of HE resolved have greater cognitive problems in relation to those cirrhotic patients without HE and how liver transplant affects such outcome in these patients. We performed two distinct meta-analysis of continuous outcomes. In both cases the results were pooled using random-effects models. Our results showed that cirrhotic patients with HE have worsened performances than cirrhotic patients and the liver transplant does not restore the cognitive capability.